Cross-country income differences and technology diffusion in a competitive world - Andreas Irmen (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper develops a new open-economy endogenous growth model where technology diffusion allows for a stable and non-degenerate world income distribution. In accordance with the empirical literature, I find that country characteristics such as the social infrastructure, the degree of openness, the investment rate, population growth, the level of human capital, or growth policies such as subsidies to innovation investments explain a country's position in the eventual world income distribution. Club convergence in growth rates can be traced back to a country's openness and to a minimum required level of human capital.
Keywords: O11; O33; O41; 330; Capital accumulation; technology diffusion; neoclassical growth model; Einkommensverteilung; Weltwirtschaft; Entwicklungskonvergenz; Technologietransfer; Innovationsdiffusion; Neue Wachstumstheorie; Offene Volkswirtschaft; Internationaler Wettbewerb; Theorie